2016
DOI: 10.3945/ajcn.116.130146
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum retinol and β-carotene concentrations and neonatal bone mineralization: results from the Southampton Women’s Survey cohort

Abstract: Background: Studies in older adults and animals have suggested contrasting relations between bone health and different vitamin A compounds. To our knowledge, the associations between maternal vitamin A status and offspring bone development have not previously been elucidated.Objective: We examined the associations between maternal serum retinol and β-carotene concentrations during late pregnancy and offspring bone mineralization assessed at birth with the use of dual-energy X-ray absorptiometry.Design: In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
(35 reference statements)
4
15
0
Order By: Relevance
“…In context with previous published observational evidence [7,8,[32][33][34][35][36][37][38][39], mother-offspring cohorts have suggested that factors such as maternal diet, lifestyle, physical activity, hormones, and vitamin D status during pregnancy were all associated with bone development in the offspring at birth, before puberty, or during adolescence, which may support the findings of this review.…”
Section: Discussionsupporting
confidence: 89%
“…In context with previous published observational evidence [7,8,[32][33][34][35][36][37][38][39], mother-offspring cohorts have suggested that factors such as maternal diet, lifestyle, physical activity, hormones, and vitamin D status during pregnancy were all associated with bone development in the offspring at birth, before puberty, or during adolescence, which may support the findings of this review.…”
Section: Discussionsupporting
confidence: 89%
“…Instead, the major direct short-term effect of a high vitamin A intake in young rats is a reduction in bone diameter. In this context we find it interesting that higher maternal serum retinol levels in late pregnancy was recently shown to be associated with lower offspring total body BMC and bone area, but not BMD ( 21 ).…”
Section: Discussionmentioning
confidence: 86%
“…Higher prepregnancy VA intake was also associated with lessened effects of pollutant exposure on birth length, compared with lower VA intake (β = −0.3 compared with −1.1, respectively) ( 122 ). A 2016 cohort study discovered that serum retinol concentration was negatively associated with child weight, bone mineral content, and bone area at birth ( 139 ).…”
Section: Resultsmentioning
confidence: 99%
“…In human trials, maternal β-carotene intakes were correlated with maternal plasma concentrations in early pregnancy, at delivery, and with cord blood β-carotene concentrations ( 41 ), as well as in cord blood ( 213 ). In a 2016 cohort study that investigated offspring bone mineral content and bone area, maternal β-carotene concentrations were inversely related to neonatal bone mineralization, in spite of direct association of maternal serum retinol with the outcome ( 139 ). In a 2005 investigation of antenatal dietary intake of antioxidant vitamins on maternal and cord plasma concentrations, plasma concentrations of VA at birth were slightly lower in cord blood than in mothers, and the association lost significance after adjusting for energy.…”
Section: Resultsmentioning
confidence: 99%